Cytokinins in Rhizopogon roseolus Secretion of N-[9-(β-d-Ribofuranosyl-9H) Purin-6-Ylcarbamoyl]Threonine into the Culture Medium - Laloue, Michel (1973)
Rhizopogon roseolus excretes the transfer RNA component, N-[9-(β-d-ribofuranosyl-9H) purin-6-ylcarbamoyl]threonine (Ado-CO-thr) into the culture medium. This compound was proposed to be the archetype of ureidopurines exhibiting cytokinin activity. The amount of Ado-CO-thr isolated from the medium is about one-twentieth the amount of ribosylzeatin that can be isolated.